Proposed Marketing Strategy for Business-to-Business (Case Study: Kijang) - Keisa Nadya Sopha; Atik Aprianingsih (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
In 2020 the clothing industry experienced a contraction due to the COVID-19 pandemic, which reduced people's purchasing power and economic activity. The pandemic has caused a shift in business transactions from offline to online, impacting consumers and business players. As a clothing producer, Kijang needs help marketing its products. The pandemic is challenging for B2B firms to adapt to the new situation. New strategies need to be formed coupled with more complex consumer behavior. Consumer analysis was conducted by conducting interviews with several wholesalers regarding the needs and wants in finding suppliers in the digital era to become the basis for designing new marketing strategies. The results showed that respondents still prioritized direct supplier searches. However, they have started looking for online suppliers as an alternative. The researcher summarizes the needs of respondents as follows having access to check product materials directly through online purchases, obtaining price information for comparison purposes, guarantees to receive good products, obtaining information about products to be sent, and general supplier information.